2012
DOI: 10.1002/cjoc.201100666
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Behavior of Pyridinecarboxylatesilver(I) Complexes

Abstract: FT-IR spectroscopy of carboxylic groups and viability tests were useful to understand the antibacterial properties of six highly efficient silver(I) pyridinecarboxylate (nicotinic, picolinic and isonicotinic acids) and bipiridinecarboxylate (pyridine-2,3-dicarboxylic, pyridine-2,4-dicarboxylic and pyridine-2,5-dicarboxylic acids) complexes with Ag-O and Ag-N bonds against E. coli (ATCC 25922) and Streptococcus agalactiae (ISP 329-09). The results show a tendency between the nature of Ag-X (X=oxygen and nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…In the upper right image ( Figure 6 c), contamination of E. coli was observed, which appears to be more sensitive to wall rupture and condensation of cytoplasmic material than is S. epidermidis . This concurs with the results of other viability studies [ 24 , 25 , 26 , 27 ], which have shown higher mortality rates for E. coli .…”
Section: Resultssupporting
confidence: 92%
“…In the upper right image ( Figure 6 c), contamination of E. coli was observed, which appears to be more sensitive to wall rupture and condensation of cytoplasmic material than is S. epidermidis . This concurs with the results of other viability studies [ 24 , 25 , 26 , 27 ], which have shown higher mortality rates for E. coli .…”
Section: Resultssupporting
confidence: 92%
“…Ag(I) pyridinecarboxylates are extensively studied as prospective antibody agents. Their structural [29][30][31][32], spectral [22,33,34], thermal [34], antibacterial [22,34] and antifungal [34] properties have been described.…”
Section: Introductionmentioning
confidence: 98%
“…Three ligand approaches are suggested [19][20][21][22]: transporters, which provide metal transport to infection, carriers which provide metal transport and its gradual delivery, multifunctional ligands, that can act as transporters, carriers and antibiotics or analgetics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is has a negative or positive effect on the target bacterial organism or biological function [11]. e most common choice of ligands is either the Schiff base ligands [13][14][15][16] or heterocyclic polypyridyl ligands, with the latter being the most common [17][18][19][20][21][22]. Polypyridyl ligands have one or more pyridine rings, and these are important ligands in coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%